Testicular regression syndrome in children: a retrospective analysis of diagnostic and laparoscopic findings - Nguyen Thi Mai, Thuy; Do Van, Khang (Frontiers in Pediatrics, 2026)
PurposeTesticular regression syndrome (TRS) is a cause of nonpalpable testis resulting from prenatal testicular involution. This study aims to describe clinical, ultrasonographic, and laparoscopic characteristics and surgical management of TRS, and to evaluate the necessity of inguinal exploration following laparoscopy.Materials and methodsA retrospective descriptive study was conducted on boys <16 years who underwent laparoscopic exploration for unilateral intra-abdominal nonpalpable testes at Vietnam National Children's Hospital between January 2021 and October 2025 and were diagnosed intraoperatively with TRS. Data collected included age, laterality, ultrasonographic findings, laparoscopic features, the decision to perform inguinal exploration, and histopathology of nubbin. Contralateral testicular size was measured by ultrasonography and compared with age-matched normal values, with p < 0.05 considered statistically significant.ResultsForty-three patients were included; median age at surgery was 26 months (range 9–156 months), and 32 cases (74.4%) involved the left side. Ultrasonography yielded false-positive findings in 12 cases (27.9%). Contralateral testicular volume was larger than normal in children <24 months (0.86 ± 0.23 vs. 0.44 ± 0.14 mL; p < 0.001) and 24–60 months (0.90 ± 0.44 vs. 0.57 ± 0.16 mL; p = 0.025), but not in those >60 months (p = 0.263). Spermatic vessels and vas deferens terminated proximal to the ring in 3 cases (7.0%) and traversed the ring in 40 cases (93.0%). Inguinal exploration was performed in 17/43 patients (39.5%), revealing and excising 13 testicular remnants (30.2%). Specimens sent for histopathology showed no testicular or seminiferous tissue.ConclusionsTesticular regression syndrome (TRS) is characterized by left-sided predominance and age-dependent compensatory hypertrophy of the contralateral testis. Ultrasonography is unreliable for diagnosis. While inguinal exploration frequently identifies fibrous remnants containing histological markers of regression, the clinical necessity of routine excision remains debated. We advocate for an individualized management approach that balances the benefits of definitive diagnosis against the low risk of malignancy.